The controversy over the restructuring of perinatal emergency services in Portugal and the importance of citizen participation in health care decision-making processes - Ana Raquel Matos (História, Ciências, Saúde: Manguinhos)
This article explores the controversial decision made by the Ministry of Health to restructure the perinatal emergency services in Portugal in 2006. Particular emphasis is given to the protests held across the country against, the actors involved, and the arguments put forward for and against the measure, in an attempt to understand the forms of knowledge and experiences brought to the discussion about the issues raised by the decision, and how different forms of knowledge are reconciled under a democratic process. In addition, this article explores the importance of citizen participation, including that which emerges from conflicting relations, in the formulation of health policies.